2018
DOI: 10.1016/j.nicl.2017.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Combining viscoelasticity, diffusivity and volume of the hippocampus for the diagnosis of Alzheimer's disease based on magnetic resonance imaging

Abstract: Dementia due to Alzheimer's Disease (AD) is a neurodegenerative disease for which treatment strategies at an early stage are of great clinical importance. So far, there is still a lack of non-invasive diagnostic tools to sensitively detect AD in early stages and to predict individual disease progression. Magnetic resonance elastography (MRE) of the brain may be a promising novel tool. In this proof-of-concept study, we investigated whether multifrequency-MRE (MMRE) can detect differences in hippocampal stiffne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 63 publications
3
67
1
Order By: Relevance
“…Our results may reflect the fact that we made reasonable effort to include only cognitively healthy participants; thus our sample may be more resilient to Hp microstructural alterations. This is especially relevant, given a recent study which found that Hp stiffness, determined using multifrequency MRE (MMRE), was lower in patients with AD when compared with healthy older adult controls ( Gerischer et al., 2017 ). Taken together, we can speculate that Hp stiffness may be maintained across the life span until the point of AD neurodegeneration, suggesting that MRE may be a promising noninvasive biomarker for early diagnosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results may reflect the fact that we made reasonable effort to include only cognitively healthy participants; thus our sample may be more resilient to Hp microstructural alterations. This is especially relevant, given a recent study which found that Hp stiffness, determined using multifrequency MRE (MMRE), was lower in patients with AD when compared with healthy older adult controls ( Gerischer et al., 2017 ). Taken together, we can speculate that Hp stiffness may be maintained across the life span until the point of AD neurodegeneration, suggesting that MRE may be a promising noninvasive biomarker for early diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…Alterations in the mechanical properties of the brain, therefore, provide a unique contrast mechanism that appears to reflect the integrity of the underlying microstructure and health of brain tissue ( Sack et al., 2013 ). The sensitivity of MRE measures is confirmed by the observation of tissue softening in many neurological diseases ( Gerischer et al., 2017 , Huston et al., 2015 , Lipp et al., 2013 , Lipp et al, 2018 , Murphy et al., 2011 , Murphy et al., 2016 , Romano et al., 2014 , Streitberger et al., 2012 ), for a review, see Hiscox et al. (2016) or Murphy and Huston (2017) , with animal studies linking this softening to degree of myelin content ( Schregel, 2012 , Weickenmeier et al., 2016 , Weickenmeier et al., 2017 ), inflammation ( Riek et al., 2012 ), and a reduction in neuronal density related to a decrease in neurogenesis ( Freimann et al., 2013 , Klein et al., 2014 ).…”
Section: Introductionmentioning
confidence: 89%
“…DTI can probe the white matter pathways in the hippocampus and has previously revealed a loss of integrity with age (Yassa et al 2011) and a relationship between hippocampal mean diffusivity (MD) and verbal memory performance (van Norden et al 2012). The combination of hippocampal MRE measures, MD from DTI, and MR volumetry has recently been shown to improve the diagnostic accuracy of Alzheimer's disease (AD) (Gerischer et al 2017). Accordingly, it is conceivable to propose that a combination of imaging modalities that may include MRE could prove useful in the identification of healthy individuals at greatest risk for cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…This points towards an exciting new application of magnetic resonance elastography as a diagnostic tool to diagnose and quantify disease progression. Interestingly, however, while the stiffness seems to be a sensitive marker for taupathology, neuronal loss, and inflammation, this is not the case for amyloid-pathology [65].…”
Section: Does Our Brain Stiffness Change During Disease?mentioning
confidence: 95%
“…3.9.6, is that they do not necessarily reflect changes in the local stiffness of the solid phase, including cells and extracellular matrix, but rather changes in the overall integrity of brain tissue, including changes in fluid transport and wave propagation. Magnetic resonance elastography shows that brain tissue softens in multiple sclerosis [156,182], Alzheimer's disease [65,124], and demyelination in general [149]. Interestingly, these softening effects scale with disease stage [86].…”
Section: Does Our Brain Stiffness Change During Disease?mentioning
confidence: 99%